Increasing baseball revenue from the female market - Dodds, Mark (SAGE Knowledge. Cases., 2015)
Claire Monroe was challenged to increase a minor league baseball team's revenue and was in charge of developing a marketing plan to target female baseball fans. This would be a new target market for the team. The increasing female fan base can create revenue for baseball franchises through ticket, merchandise, and concession sales, as well as connecting with sponsors who specifically target female customers. Although there are many gender similarities in regards to fan avidity, there are important differences between the sexes in terms of motivation, media, and merchandise needs. Claire must research the target audience, analyze marketing research data, and make recommendations to increase female attendance to have those women spend more money on baseball-related items.